A qualitative study exploring the impact of COVID on mental health and wellbeing of employees in India - Logchander, Kiranchander (2022)
COVID 19 has shaped the world as we know now in the past two years with its devastating impact in all our lives. There has been a huge difference in people pre and post pandemic as they endured the ordeal brought by the deadly disease both physically and mentally. As an employee working during this period in India there is bound to be an impact caused by this pandemic on their mental health. There were several challenges faced by employees during this period and a lot of factors that contributed to the affecting of mental health. Many of the challenges include surviving the pandemic, working from home, providing, and supporting their families. The employees had to balance work and life, endure social isolation due to the pandemic which all resulted in taking a toll on their mental health. The study aims to identify how all these factors impacted the mental health of Indian employees during this period. The study utilizes a qualitative research method. It utilises semi structured interviews to collect the necessary data. The data thus collected is analysed using thematic analysis which groups the data into common themes, comparing them to previous research to get new results.